Peran Kepemimpinan Kepala Sekolah Perempuan dalam Meningkatkan Kinerja Guru di SDN 1 Langkaplancar - Yudi Saputra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
The principal leadership is an important position in the running of the wheels of education Leadership styles can be influenced by gender positions. Especially in improving teacher performance. This research uses a qualitative approach with phenomenological methods that use data collection techniques including interviews, observations, complete open and directed discussions, and documentation studies involving principals, and teachers. The results showed that the female leadership style at SDN 1 Langkaplancar is a transformational leadership style. Where she always has an advanced and positive outlook and movement to achieve madrasah goals together. This is reflected in the way she leads meetings, initiates ideas, and implements them through various existing programs. Another impact of women's leadership can be seen in various aspects of teacher activities at SDN 1 Langkaplancar, starting from the process of lesson planning, lesson implementation, evaluation, problem solving, student assistance, facility improvement, to the creation of programs for schools. Her intensive assistance ensures that every teacher can contribute optimally to the progress of the school.